Testing for Distortions in Performance Measures: An Application to Residual Income‐Based Measures like Economic Value Added. Issue 1 (March 2015) - Sloof, Randolph; van Praag, Mirjam
<x xml:space="preserve">Abstract</x> Distorted performance measures in compensation contracts elicit suboptimal behavioral responses that may even prove to be dysfunctional (gaming). This paper applies the empirical test developed by Courty and Marschke (Review of Economics and Statistics, 90, 428–441) to detect whether the widely used class of residual income‐based performance measures—such as economic value added (EVA)—is distorted, leading to unintended agent behavior. The paper uses a difference‐in‐differences approach to account for changes in economic circumstances and the self‐selection of firms using EVA. Our findings indicate that EVA is a distorted performance measure that elicits the gaming response.